A Rare Case of Testicular Tuberculosis Mimicking as Testicular Malignancy - S. Rishabh; K. Krishnamoorthy; T. Joseph Pratheeban; E. Mathan; O. M. Rahman Shahul Hameed (Journal of Association of Pulmonologist of Tamil Nadu)
Extrapulmonary tuberculosis (TB) represents 10%–15% of TB cases, with lymph nodes being the most frequent site in India. Genital TB is uncommon, and testicular TB is rarer, still accounting for only 3% of genital TB cases. Isolated testicular TB is extremely rare and often mimics other testicular conditions, such as malignancy, complicating diagnosis. We present a case involving a 49-year-old male with diabetes and a history of smoking, who experienced bilateral scrotal swelling and pain over 3 months, accompanied by weight loss. He had no history of respiratory complaints, fever, TB, or significant medical history. Physical examination revealed bilateral scrotal swelling (3 cm × 3 cm) and multiple inguinal lymph nodes. Scrotal ultrasound demonstrated bilateral heterogeneously hypoechoic masses, while magnetic resonance imaging of the scrotum and testis identified solid cystic lesions with heterogeneous enhancement. Serum alpha-fetoprotein and lactate dehydrogenase levels were within normal limits. Fluorodeoxyglucose positron emission tomography–computed tomography revealed metabolically active lesions in both testes and several lymph nodes. Chest X-ray was normal. With a strong suspicion of malignancy, the patient underwent bilateral high inguinal orchiectomy. Histopathological analysis of the excised tissue showed dense epithelioid granulomas with caseous necrosis, indicative of TB. The patient was commenced on antitubercular therapy, with plans for continued monitoring. Although rare, isolated testicular TB should be included in the differential diagnosis of testicular masses. Prompt recognition and appropriate treatment are essential to prevent unnecessary surgical procedures and ensure optimal management.